Humanistic Human Resource Management in the Digital Era - Ispini, Sri (Jurnal Ekonomi, Manajemen, dan Bisnis, 2023)
The advancement of digital technology has significantly reshaped human resource management (HRM), presenting both efficiency gains and human challenges. This study aims to formulate a conceptual model of humanistic HRM in the digital era, balancing technological efficiency with human values. Employing a qualitative-descriptive approach through a systematic literature review, the research synthesizes global studies and reports relevant to humanistic management and digital transformation in HRM. The results reveal that technology adoption without human orientation may lead to dehumanization, digital fatigue, and reduced employee engagement. Conversely, integrating humanistic principles such as responsible flexibility, empathetic leadership, and ethical data governance enhances well-being and sustainable performance. The study contributes to the development of a Humanistic-Digital HRM paradigm, positioning technology as a means to strengthen human dignity rather than replace it. These findings provide a conceptual foundation for organizations to manage HR ethically, meaningfully, and sustainably amid ongoing digital transformation